Can international junior success predict international senior success? A case study in elite table tennis - Li, P.; de Bosscher, V.; Pion, J. (Science and Racket Sports VI, 2019)
Little is known about the extent to which junior success can be used to predict senior success. Some studies have demonstrated a minor relationship between athletes` junior success and senior success. However, these studies mainly focus on successes that athletes achieved at junior competitions. Successes that players achieved at international senior competitions but at a junior age have been relatively ignored. This study aims to explore the role that junior performances (age <19) at different levels of competitions in predicting eventual international success in elite table tennis. The sample comprised 397 international male and female table tennis players, born between 1982 and 1990, who competed in both international junior and senior competitions between 1997 and 2016. The discriminant analysis revealed that 55.3% of the early achievers (i.e., athletes who won medals in senior competition at a junior age) and 36.7% of the junior medalists (i.e., athletes who won medals at junior competitions) were predicted to win international senior medals. The findings demonstrate that international junior success plays a critical role in later international senior success in table tennis; still, half of the senior successful players did not win medals at international competitions at a junior age.